Improving the sustainability of phosphorus fertility management in Kansas - Bourns, Megan Ashley (My University, 2024)
Phosphorus (P) is an essential nutrient for crop production, often required in fertilizer form for optimum agronomic productivity; however, P loss from agricultural fields in runoff water poses a substantial environmental threat. Lost P contributes to P loading, eutrophication, and development of harmful algal blooms in surface water bodies. Because of the consequences of P loss, agronomic management of P has been under scrutiny in recent years, in an effort to develop best management practices around P fertilization and fertility management. Strategies are required that align both agronomic productivity and environmental protection goals. A long-term study was developed at Ashland Bottoms, KS, to investigate the interaction between P fertilizer management strategies and cover crop use to manage P loss, in a corn (Zea mays)-soybean (Glycine max) cropping system. The study began with a build phase wherein soil P was increased, focused on the placement and timing effects of P fertilizer. Treatments included a zero P control (CN), fall broadcast (FB), and spring injected (SI) P fertilizer. Each of these treatments was expressed with (CC) and without (NC) a cover crop. The study then transitioned to a maintenance/drawdown period from 2020-2022; the treatments during this time included the two levels of cover crop (CC and NC), CN P fertilizer management, drawdown (DD) and build and maintain (BM) management. During the build phase, both FB and SI P fertilizer management increased P access and utilization for the main crop and cover crop. Cover crop did not affect main crop P uptake, removal in grain, or return to soil in crop residue, but CC treatment increased total P uptake and return in the system. Cover crop effects on P uptake, removal, and return were the same regardless of P fertilization treatments. Phosphorus fertilizer and CC treatments did not affect agronomic P use efficiency. Both FB and SI P fertilizer management decreased environmental P use efficiency, although SI tended to decrease it less than FB. The cover crop significantly improved environmental efficiency only in 2019, when it reduced erosion losses. Therefore, cover crops were not consistently beneficial for reducing environmental effects of P fertilization, and their use cannot replace the importance of sound P fertilizer stewardship, including sub-surface P placement. However, cover crops play an important role in improving environmental efficiency in years with high erosion loss potential. During the maintenance/drawdown phase, CC decreased main crop biomass for all P fertilizer management treatments, but did not affect P access or use by corn or soybean. Phosphorus nutrition was generally similar for both DD and BM management, with the exception of grain P removal in corn under CC management; BM increased grain P removal in corn significantly when a cover crop was used, compared to DD management under CC treatment. During the three years of the maintenance/drawdown phase, DD management under NC was consistently most profitable. This was true even when corn yield was significantly lower with DD management compared to BM; in other words, the increased corn yield was not enough to offset the increased cost of BM management compared to DD, for that year. While STP did decline under DD management and P fertilization was withheld, improvement in water quality relative to BM was not consistent across all metrics. The DD and CC combination reduced P losses in just one of three years. On the other hand, CN P fertilizer management consistently reduced P losses; however, CN management is not a profitable option for producers and substantial incentives would be required for adoption of CN management as a conservation option. Further research is needed to determine the feasibility of drawdown under initially high STP as a mode to improve annual return, reduce P inputs, and reduce P loss from the system over time. Historical data analysis and new field studies were conducted in KS to determine the feasibility of a new P fertilizer management paradigm, sustainable sufficiency (SSF). The SSF paradigm is based on establishing a lower STP threshold for maintenance, maintained through routine applications of P fertilizer at crop removal rates. Historical data analysis revealed there is no clear STP threshold for maintenance based on existing P rate studies from the state; however, P fertilization rates greater than crop removal were only needed 9% of the time to obtain optimum yield. This suggests there is likely room to explore maintenance thresholds below the current critical threshold for yield response. Field studies were used to evaluate the relationship between initial STP and relative yield of corn and soybean with a maintenance rate of P fertilizer applied. Higher STP did not increase corn and soybean yield with a maintenance rate of P fertilizer, indicating it should be possible to lower the STP threshold for maintenance management.
Keywords: Phosphorus; Fertilizer management; Water quality; Corn; Soybean